The Influence and Dynamics of Islamic Civilization in the Archipelag - Wijaya Wijaya; Vicheka Rith; Chenda Dara (Yayasan Adra Karima Hubbi, 2025)
This study examines the dynamics and civilization of Islam in the Nusantara with a focus on intercultural interactions that shape the social and cultural structures in this region. Islam, which came through trade and da'wah routes, played an important role in shaping civilization in the Nusantara through the exchange of science, technology, and adaptation of local culture. The great contribution of Muslim scientists in the fields of mathematics, medicine, and philosophy also influenced the development of science in the Nusantara. Meanwhile, cultural interactions between Islam and local cultures resulted in acculturation that enriched the heritage of Nusantara arts and culture, such as performing arts and gamelan music. This study uses a qualitative approach with literature study methods and historical analysis to explore how Islamic civilization adapted and developed in the Nusantara, and how it influenced local social, legal, and cultural structures. In conclusion, Islamic civilization in the Nusantara is not only limited to religious aspects, but also includes social, economic, and cultural fields that are interrelated and shape the identity of the Muslim community in the Nusantara.